2020
DOI: 10.29342/cnj.v3i3.118
|View full text |Cite
|
Sign up to set email alerts
|

Manifestasi Klinis Neurologis Pada Covid-19

Abstract: Latar Belakang: Coronavirus Disease 2019 (COVID-19) yang disebabkan oleh virus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) merupakan penyakit yang mudah menular dan menyebabkan kondisi pandemi saat ini. Manifestasi utama infeksi SARS-CoV-2 adalah gangguan sistem respirasi, tetapi manifestasi neurologis telah dilaporkan pada beberapa literatur. Tujuan: Untuk menggambarkan manifestasi klinis neurologis yang dapat ditemukan pada pasien COVID-19. Diskusi: Gejala neurologis yang dapat timbul pada C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(71 reference statements)
0
4
0
1
Order By: Relevance
“…patients occurs due to significant damage to the nucleus of olfactory epithelial cells due to infection of supporting cells and vascular pericytes of the epithelium and olfactory bulb [9], [17]. [1], [7], [15], [19]. Another hypothesis suggests that anosmia occurs due to neuronal death caused by a cytokine storm, specifically the role of IL-6 produced by neurons through stimulation of the SARS-CoV-2 virus spike protein [1], [4]- [6], [20].…”
Section: Resultsmentioning
confidence: 99%
“…patients occurs due to significant damage to the nucleus of olfactory epithelial cells due to infection of supporting cells and vascular pericytes of the epithelium and olfactory bulb [9], [17]. [1], [7], [15], [19]. Another hypothesis suggests that anosmia occurs due to neuronal death caused by a cytokine storm, specifically the role of IL-6 produced by neurons through stimulation of the SARS-CoV-2 virus spike protein [1], [4]- [6], [20].…”
Section: Resultsmentioning
confidence: 99%
“…A study reported the prevalence of altered consciousness in COVID-19 patients ranging from 1.4% to 6.9%, with a higher incidence in patients with comorbidities or critical conditions. Altered consciousness was associated with various causes such as encephalopathy, sepsis, and metabolic disorders [ 28 ]. This study demonstrated a relationship between sex with myopathy and altered consciousness, whereas there was no association between age with myopathy and altered consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…In confirming the results, a study found that the most common neurological symptom among COVID-19 patients was headache, occurring in at least 6.5% of cases. Headaches can also manifest as the initial and only symptom in infected individuals [19,20,[23][24][25][26][27][28][29][30]. Additionally, a study reported a prevalence of approximately 12% for headaches among COVID-19 patients, with many patients encountering headaches as their initial symptom.…”
Section: Short Communicationmentioning
confidence: 99%
“…SARS-CoV-2, also known as the coronavirus, is a disease that spreads quickly and can lead to pandemic circumstances. Infection with SARS-CoV-2 primarily manifests as respiratory system diseases [1]. Gas exchange during respiration includes the exchange of carbon dioxide (CO2) and oxygen (O2), which the body needs for cellular metabolism [2].…”
Section: Introductionmentioning
confidence: 99%